The economic sustainability of smallholder tea production systems in Tanzania - Simbua, E. F. (Cranfield University, 2006)
Tea is an important crop in Tanzania, contributing over US$45 million to exports each year. It is grown by over 30,000 smallholder households, and a further 10,000 people are employed in the estates sector. In this context, this study explores the current and potential contribution of the smallholder tea sector towards economic sustainability of the Tanzanian tea industry and rural livelihoods. Following literature review and an exploratory study of key stakeholders, a methodology incorporating two main components, an Asset Based Model of Sustainability and a Value Chain Assessment Model, was developed and applied to assess the sustainability of the smallholder tea production systems. The tea based livelihood systems and the associated tea value chains for three case study areas were compared involving a survey of over 300 tea growing and over 100 non-tea growing households, and three processing factories. The study showed that there is an existing synergy between processing factories and smallholder producers which is important for the future development as factories are set to expand the volume of greenleaf sourced from smallholders. At farm level, greenleaf prices, yield, access to input credit, access to research and extension support, availability of farm labour, and access to a reliable greenleaf markets were identified as critical factors that influence the livelihood of the tea growing households. The quantitative analysis showed clear association between farmers involvement in tea production and accumulation of assets (natural, physical and financial), confirming the role of tea in supporting livelihoods. The study concludes that the smallholder tea production systems can contribute to sustainable livelihood systems. Finally the study gives recommendation for various groups of stakeholders regarding ways to improve the performance of the smallholder production systems.